Rhodium(I)-Catalyzed Carbonylative Arylation of Alkynes with Arylboronic Acids Using Formaldehyde as a Carbonyl Source - Wang, Chuang; Morimoto, Tsumoru; Kanashiro, Hiroyuki; Tanimoto, Hiroki; Nishiyama, Yasuhiro; Kakiuchi, Kiyomi; Artok, Levent (Synlett, 2014)
The rhodium(I)-catalyzed reaction of alkynes with arylboronic acids in the presence of formaldehyde resulted in a carbon monoxide gas-free carbonylative arylation to yield α,β-enones. The simultaneous loading of phosphine-ligated and phosphine-free rhodium(I) complexes is required for efficient catalysis, which catalyze the abstraction of a carbonyl moiety from formaldehyde (decarbonylation) and its subsequent introduction into the substrate (carbonylation), respectively.
Keywords: carbonylation; arylation; rhodium; formaldehyde; alkynes